PENINGKATAN KETERAMPILAN MENULIS PARAGRAF DESKRIPSI MELALUI MODEL PEMBELAJARAN TERSTRUKTUR SISWA KELAS XI SMK NEGERI 1 JENEPONTO - Hj. Syamsinar Hj. Syamsinar (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2017)
This research is a classroom action research that aims to describe the ability of writing paragraphs through structured learning method of students of class XI SMK Negeri 1 Jeneponto. The population of this study is the total students of class XI SMK Negeri 1 Jeneponto, which amounted to 132 people who are divided into four parallel classes. The sampling of this research using random sampling technique and assigned the class that used as sample is class XI-1 which amounted to 35 people. The study was conducted in two cycles. Each cycle through three stages, namely (1) planning, (2) action and observation, and (3) reflection. Data collection techniques used are observation, documentation, and tests. Analytical technique using qualitative descriptive analysis technique of flow model proposed by Milles and Huberman consist of three activity flow which happened simultaneously, that is data reduction, data presentation, and conclusion / verification. The results showed that the application of Structured Learning Methods can Increase Learning Outcomes Writing Paragraph Students Class XI SMK Negeri 1 Jeneponto. Improved learning outcomes appear in the implementation of actions in cycles I and II that show a change in behavior and student learning outcomes in a more positive direction. As an application of this research, it is suggested to (1) Indonesian Language and Literature Teachers, especially Indonesian Language and Literature Teachers of SMK Negeri 1 Jeneponto to apply structured learning method as one of paragulation writing method. (2) Students should practice more in improving the ability to write paragraphs and consider the activity of writing paragraphs as a fun activity.